Socio-economic Impact in a Region in the Southern Part of Jutland by the Establishment of a Plant for Processing of Bio Ethanol - Henning P. Jørgensen; Kurt Hjort-Gregersen (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2005)
A cooperation between The Farmers Association of Southern Jutland, Institute of Food Economics Department of Environmental and Business Economics, USD, and Centre for Rural Development, hosting Leader+ Denmark This report is a translation of the original report in Danish: (Jørgensen, H. P. and K. H.-Gregersen: Estimerede økonomiske virkninger i Syd- og Sønderjyl-land ved etablering af et anlæg til fremstilling af bioethanol, September 2003).
Keywords: 330; Petrochemische Industrie; Biokraftstoff; Agrarproduktion; Regionales Wachstum; Dänemark